AN ANALYSIS OF GRAMMATICAL ERRORS MADE BY THE TENTH GRADE STUDENTS OF SMAN 12 PEKANBARU IN WRITING RECOUNT TEXTS - Destriani Destriani; Supriusman Supriusman; Dahnilsyah Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aims of this study are intended to find out the types of grammatical errors are made by the tenth grade students of SMAN 12 Pekanbaru academic year 2018/2019 in writing recount texts. The error collected was classified based on Corder’s theory. This research used a descriptive method. The participants of this research were 65 students of class X MIPA 3 and class X IPS 6 of SMAN 12 Pekanbaru. The students were selected to be the sample using cluster sampling technique. The writer collected the data by using a writing test with the topic “unforgettable Experience. This research showed that the students made errors into four types: error of omission, error of addition, error of selection and error of ordering. The research findings provide the most common types of errors made by the students was error of selection with the number of error was 363 or 67%. Moreover, it is followed by error of omission with the number of error 93 or 17.2%, error of addition with the number 62 or 11.40%, and whereas, for error of ordering only took 24 or 4.40%. The errors performed by the students of tenth grade of SMAN12 Pekanbaru were caused by the influence of the first language and the second language.Key Words: Error, Error Analysis, writing, Recount Text